2016
DOI: 10.1364/ao.55.009384
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-flat supercontinuum generated from high-power, picosecond telecommunication fiber laser source

Abstract: An ultra-flat, high-power supercontinuum generated from a picosecond telecommunication fiber laser was presented. The pulse from a carbon nanotube mode-locked oscillator was amplified using an Er-Yb codoped fiber amplifier. The output of the system achieved an average power of 2.7 W, with the center wavelength at 1564 nm and a FWHM of 6 nm in the spectral domain. By passing this amplified high-power pulse through a 4.6 m highly nonlinear photonic crystal fiber, an ultra-flat supercontinuum spanning 1600-2180 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Lasers exhibit exceptional characteristics, including tunable color, narrow line width, high intensity, and long coherence length, that have been applied to revolutionize processes in fields such as material processing, medicine, biology, and telecommunications. In those applications, inorganic compounds, including semiconductors and doped crystals, have generally been used as gain media. , In addition, the resonators have consisted of sensitive optomechanical parts or special reflectors made of metals, dielectrics, or plastics. The gain and cavity materials are usually inelastic, unbendable, and manufactured in processes that often require toxic precursors in vacuum environments at high temperatures. , …”
Section: Introductionmentioning
confidence: 99%
“…Lasers exhibit exceptional characteristics, including tunable color, narrow line width, high intensity, and long coherence length, that have been applied to revolutionize processes in fields such as material processing, medicine, biology, and telecommunications. In those applications, inorganic compounds, including semiconductors and doped crystals, have generally been used as gain media. , In addition, the resonators have consisted of sensitive optomechanical parts or special reflectors made of metals, dielectrics, or plastics. The gain and cavity materials are usually inelastic, unbendable, and manufactured in processes that often require toxic precursors in vacuum environments at high temperatures. , …”
Section: Introductionmentioning
confidence: 99%
“…By using ideal pedestal-free Raman shifted solitons in a highly nonlinear fiber (HNLF), they reported a high degree of flatness of 1 dB for a 520 nm SC bandwidth in the range from 1370 to 1890 nm [23]. Since then, many SC schemes with ultra-flat characteristics have been reported based on pedestal-free pump pulses in the normal and anomalous dispersion regimes [24][25][26][27][28]. Recently, mode-locked fiber laser (MLFLs) generating the so-called noise-like pulses (NLPs) have been proposed as the pump sources to realize spectral broadening in different kinds of optical fibers [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…By using ideal pedestal-free Raman shifted solitons in a highly nonlinear fiber (HNLF), they reported a high degree of flatness of ~1 dB for a 520 nm SC bandwidth in the range from 1370 to 1890 nm [23]. Since then, many SC schemes with ultraflat characteristics have been reported based on pedestal-free pump pulses in the normal and anomalous dispersion regimes [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al demonstrated the generation of SC with high atness and no ne structure by using pedestal less picosecond pump pulses with kW, MW or even higher peak power. They obtained SC with high atness in the range of 1600-2180 nm by launching pedestal less picosecond pulses with a central wavelength of 1564 nm into highly nonlinear photonic crystal bers (HNLF-PCF) under the condition of all normal dispersion (ANDi) [14]. However, since picosecond or longer width pulses will cause nonlinear ampli cation of noise signals in nonlinear bers [15,16], unstable ne structures will exist in the spectrum, which can be signi cantly improved by using femtosecond pulses with low soliton orders as pump sources.…”
Section: Introductionmentioning
confidence: 99%